2017
DOI: 10.2147/jpr.s119820
|View full text |Cite
|
Sign up to set email alerts
|

Bay11-7082 attenuates neuropathic pain via inhibition of nuclear factor-kappa B and nucleotide-binding domain-like receptor protein 3 inflammasome activation in dorsal root ganglions in a rat model of lumbar disc herniation

Abstract: Lumbar disc herniation (LDH) is an important cause of radiculopathy, but the underlying mechanisms are incompletely understood. Many studies suggested that local inflammation, rather than mechanical compression, results in radiculopathy induced by LDH. On the molecular and cellular level, nuclear factor-kappa B (NF-κB) and nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome have been implicated in the regulation of neuroinflammation formation and progression. In this study, the autologous nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“… 43 , 46 For example, using potential inhibitor BAY11–7082 or transgenic inhibition to reduce NF-кB activation in the DRG level or spinal level reduces pain behavior and inflammation after peripheral nerve injury and attenuates neuropathic pain. 47 , 48 Our study showed that intrathecal injection of NF-кB inhibitor at ninth day after modeling attenuated tumor induced hypersensitivity and decreased MCP-1 and CCR2 level in spinal cord, supporting the involvement of NF-кB in the development and maintenance of CIBP via MCP-1 and CCR2 produce in the spinal cord. Furthermore, our results showed NF-кB to be predominantly expressed in neurons of the spinal cord after modeling.…”
Section: Discussionsupporting
confidence: 61%
“… 43 , 46 For example, using potential inhibitor BAY11–7082 or transgenic inhibition to reduce NF-кB activation in the DRG level or spinal level reduces pain behavior and inflammation after peripheral nerve injury and attenuates neuropathic pain. 47 , 48 Our study showed that intrathecal injection of NF-кB inhibitor at ninth day after modeling attenuated tumor induced hypersensitivity and decreased MCP-1 and CCR2 level in spinal cord, supporting the involvement of NF-кB in the development and maintenance of CIBP via MCP-1 and CCR2 produce in the spinal cord. Furthermore, our results showed NF-кB to be predominantly expressed in neurons of the spinal cord after modeling.…”
Section: Discussionsupporting
confidence: 61%
“…At 10 μM (BAY11-7082), secretory VEGF was reduced by ~40% compared to SAA alone and this concentration of the NFB inhibitor (BAY11-7082) was selected for all further studies on gene and protein analysis. This selected (active) dose of BAY11-7082 (10 μM) is lower than that used by others [28,29] and provides an advantage of minimising potential non-specific inhibitory activity in cultured HCtAEC.…”
Section: Resultsmentioning
confidence: 99%
“…At 10 μM (BAY11-7082), secretory VEGF was reduced by ~40% compared to SAA alone and this concentration of the NFκB inhibitor (BAY11-7082) was selected for all further studies on gene and protein analysis. This selected (active) dose of BAY11-7082 (10 μM) is lower than that used by others [28,29] and provides an advantage of minimising potential non-specific inhibitory activity in cultured HCtAEC.…”
Section: Resultsmentioning
confidence: 99%